Effective and selective adsorption of methyl tert-butyl ether on ZSM-5 zeolite: a comparative study - Hua, Tingyu; Li, Shanshan; Hu, Jingli; Yan, Wei (Frontiers in Chemistry, 2024)
The extensive use of methyl tert-butyl ether (MTBE) as a gasoline additive has caused serious environmental problems that need to be addressed urgently. The feasibility of remediation of MTBE-contaminated groundwater by ZSM-5 zeolite with SiO2/Al2O3 ratio of 50/130/360 was explored. The SiO2/Al2O3 ratio had a great influence on the physicochemical properties and structure, as well as the adsorption and mass transfer of MTBE on ZSM-5. The adsorption of MTBE on zeolites with SiO2/Al2O3 ratios of 50 and 130/360 followed the Langmuir and Freundlich models, respectively, and was controlled by different mass transfer processes. The morphology and adsorption capacity of ZSM-5 (50) and ZSM-5 (130) differed significantly, while the differences between ZSM5-(130) and ZSM-5 (360) were less pronounced. ZSM-5 (360) had higher adsorption capacity and adsorption efficiency for MTBE, and the larger BET surface area, pore volume and stronger hydrophobicity were the key factors to promote MTBE adsorption. Compared to activated carbon (AC), ZSM-5 (360) was more effective for MTBE removal at low concentrations (≤200 mg·L−1) and had the advantage of selective adsorption of MTBE with the addition of BTEX. In column adsorption, decreasing the concentration had opposite effects on MTBE removal by ZSM-5 and AC. At 5–10 mg·L−1, ZSM-5 (360) column reduced effluent concentration and improved bed utilization and removal efficiency.